2019
DOI: 10.1007/s00107-019-01482-z
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of thermally modified and pressurized hot water extracted Scots pine sapwood against decay by the brown-rot fungus Rhodonia placenta

Abstract: The thermal degradation of wood is affected by a number of process parameters, which may also cause variations in the resistance against decay fungi. This study compares changes in the chemical composition, water-related properties and decay resistance of Scots pine sapwood that was either thermally modified (TM) in dry state at elevated temperatures (≥ 185 °C) or treated in pressurized hot water at mild temperatures (≤ 170 °C). The thermal decomposition of easily degradable hemicelluloses reduced the mass los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
(66 reference statements)
3
12
0
Order By: Relevance
“…The chemical analyses confirmed earlier studies on the difference between HT of wood in dry and watersaturated state [6,26,30,31]. The presence of water catalyzed the hydrolytic cleavage of covalent bonds during the hydrothermal treatments wood [32].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The chemical analyses confirmed earlier studies on the difference between HT of wood in dry and watersaturated state [6,26,30,31]. The presence of water catalyzed the hydrolytic cleavage of covalent bonds during the hydrothermal treatments wood [32].…”
Section: Discussionsupporting
confidence: 85%
“…Some studies explained that cross-linking reactions during Dry-HT enhance the cell wall matrix stiffness and restrict the expansion of the polymers to accommodate water molecules [30,31,43]. Other studies speculated that changes in the conformation of the matrix polymers hinder the relaxation of the cell wall polymers toward their thermodynamically most favorable arrangement [31,37,44]. Similar to the reduction in wood MC, the present study also showed differences in the change in tensile properties by the two HT techniques.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Thermal modification utilizes the partial degradation of wood at elevated temperatures to enhance the hygroscopic properties and decay resistance of solid wood products [10]. While HWE is less efficient in decreasing the hygroscopicity [11,12] or decay resistance [13] of wood compared with thermal modification, it enables the utilization of removed hemicelluloses and limits the loss in strength and toughness of the solid residue [14]. However, increasing the wood size may have a significant effect on the effectiveness of HWE and the obtained treatment products.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Altgen et al (2020) have shown that a leaching process can remove the residues produced during the thermal treatment under dry or pressurized hot water conditions. One main consequence of no leaching of the samples was the eventual underestimation of the real mass loss if ones aim to compare results under such peculiar conditions.…”
Section: Mass Loss Kinetic Analysismentioning
confidence: 99%